Coordination Strategy for Changes in the Regional Medium-Term Development Plan (RPJMD) in Bandung City - Muhamad Nur Afandi; Salwa Rizki Aulia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Processes and mechanisms that are too long in the preparation of development planning documents often result in not being completed on time. This is a challenge for the Development Planning, Research and Development Agency for the City of Bandung as a technical institution that manages development planning in the City of Bandung. Leadership in coordination is still an important point in achieving the success of an organization. This study aims to overcome obstacles related to coordination during the preparation of changes to the Regional Medium-Term Development Plan (RPJMD) and to propose the formulation of a coordination strategy in the preparation of changes to development planning documents. This research was conducted using a case study method by combining qualitative and quantitative methods, especially in conducting data analysis using SWOT analysis. The results of the study indicate that there is still a lack of synchronization of understanding and action regarding the flow of mechanisms that will be taken by the parties involved. In addition, the coordination strategy that has been used by the Bandung City Regional Development Planning Agency is still not optimally carried out, causing delays in the completion of the RPJMD changes. Strategy development and renewal is one of the solutions in overcoming the lack of optimal coordination strategy in the preparation of RPJMD changes in the city of Bandung.